2007
DOI: 10.1016/j.crme.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

On Boussinesq's paradigm in nonlinear wave propagation

Abstract: Boussinesq's original derivation of his celebrated equation for surface waves on a fluid layer opened up new horizons that were to yield the concept of the soliton. The present contribution concerns the set of Boussinesq-like equations under the general title of 'Boussinesq's paradigm'. These are true bi-directional wave equations occurring in many physical instances and sharing analogous properties. The emphasis is placed: (i) on generalized Boussinesq systems that involve higher-order linear dispersion throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…Then the assumption Q = µ 0 + µ 1 Ω 2 (where µ 0 , µ 1 are positive constants) is the simplest one we can make to uncover nonlinear governing equations; it corresponds to fourth-order elasticity theory 10 . With these assumptions, equation (19) reduces to…”
Section: Travelling Waves Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then the assumption Q = µ 0 + µ 1 Ω 2 (where µ 0 , µ 1 are positive constants) is the simplest one we can make to uncover nonlinear governing equations; it corresponds to fourth-order elasticity theory 10 . With these assumptions, equation (19) reduces to…”
Section: Travelling Waves Solutionsmentioning
confidence: 99%
“…A thorough review on several mechanical aspects and applications of this equation may be found in the recent paper by Christov et al 19 . When we study travelling waves of (30) in the linearly polarized case, we obtain…”
Section: Travelling Waves Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out recently [1] that, on studying solitary waves propagating on the free surface of a constant depth fluid, Boussinesq derived initially a wellposed equation which contained a mixed fourth order derivative for the dispersion alongside with the purely spatial fourth order derivative. Then, in an attempt to find an analytical solution he went on to replace the time derivatives in the mixed derivative term by purely spatial ones using the ansatz u ;t ¼ Àcu ;x which is true for steady linear waves propagating with phase speed c. If this unnecessary ansatz was not applied by Boussinesq the form of his celebrated equation in one spatial dimension would it be in the linear regime u ;tt À c The equation we usually denote as the Boussinesq equation (BE) is obtained from (1.1) considering b 1 ¼ 0 and b 2 < 0.…”
Section: Introduction and Basic Equationsmentioning
confidence: 99%
“…The double dispersion equation (1) was introduced as a mathematical model of nonlinear dispersive waves in various contexts (see for instance [3][4][5][6] and the references therein). It belongs to the following general class of nonlocal nonlinear wave equations:…”
Section: Introductionmentioning
confidence: 99%